If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -2x = 2x + -1y Reorder the terms: -2x + 8y = 2x + -1y Solving -2x + 8y = 2x + -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2x + -2x + 8y = 2x + -2x + -1y Combine like terms: -2x + -2x = -4x -4x + 8y = 2x + -2x + -1y Combine like terms: 2x + -2x = 0 -4x + 8y = 0 + -1y -4x + 8y = -1y Add '-8y' to each side of the equation. -4x + 8y + -8y = -1y + -8y Combine like terms: 8y + -8y = 0 -4x + 0 = -1y + -8y -4x = -1y + -8y Combine like terms: -1y + -8y = -9y -4x = -9y Divide each side by '-4'. x = 2.25y Simplifying x = 2.25y
| 1.6n-72=4n-30 | | ((9ab^3)^(1/2))/((ab)^(1/2)) | | 5(a+5)=64.5 | | 12(2x+2)=60 | | 16-2y=22 | | 2y+3x=310 | | 19t-17t=16 | | 3y+2x=310 | | -3.6=4c-8 | | 3x+5+3x+5+8x-2+2x=503.4 | | http://media.education2020.com/evresources/3107-08-04/mc009-1.jpg | | 5e-8=16 | | x(3+4)= | | 3=n+5-2 | | 2y-y=20 | | log(x^2-4)=8 | | 14w-10w=20 | | x+3.2*4=223 | | 4x+10+3x-11=90 | | 13h-3h=20 | | 3(a+6)=39 | | (5x-6y)+(6x-5y)= | | 13.54m/4 | | -8(a-3)=-8a+25 | | 4x+10+3z-11=90 | | 2x-1+2x-1+4x+8=112 | | 2v-v=10 | | (3y+2)(5y^2+4y-3)= | | (5x-6y)(6x-5y)= | | 84/x=7 | | t/14=49/35 | | 9x+6+6x-6=90 |